SEMIOTICS OF ETHNOMOTIFS IN ADVERTISING: ART HISTORICAL PERSPECTIVE ON TRADITION AND MODERNITY - Сиваш, І. О. (Art and Design, 2025)
Purpose: to study the semiotic features of the use of ethnomotifs in advertising communications, to consider the artistic aspects of national symbols in advertising, to determine the balance between tradition and modernity in advertising design. Methodology is based on systemic and structural, historical and art historical, and comparative methods that allow us to identify the factors of ethnodesign, consider it as a holistic design system, and reveal the significant influence of the semiotics of ethnomotifs in advertising. Results. The semiotics of ethnomotifs in advertising and their influence on the formation of national identity are studied, since the modern advertising industry is increasingly turning to ethnomotifs, using national symbols, ornaments, colors, and cultural codes. It is also established that the use of ethnomotifs in advertising is a powerful tool for establishing an emotional connection with the consumer and emphasizing the national identity of the brand. Scientific novelty. The article reveals the significance of ethnomotifs as carriers of cultural memory, analyzes the peculiarities of their visual coding in advertising, and suggests approaches to preserving authenticity when adapting ethnic aesthetics to modern graphic solutions. Practical significance. The semiotics of ethnomotifs in advertising is an important tool for the formation of national identity, but its use requires a conscious approach. The main challenge is the need to preserve authenticity when adapting traditional aesthetics to the modern advertising space. Effective integration of ethnomotifs is possible if there is a balance between tradition and innovation, which will contribute to both the preservation of cultural heritage and the development of competitive visual branding in Ukraine.